Digitalización de datos productivos y su relación con los costos y la rentabilidad en la granja porcina Agropecuaria Lorena San Juan Bautista 2025 - Garay Vásquez, Herless Edson (2025)
The general objective of this research was to determine the relationship between the digitization of production data and costs and profitability in the Agropecuaria Lorena pig farm, located in the district of San Juan Bautista, during the year 2025. The study was developed under a quantitative approach, with a quasi-experimental design and correlational scope. The information was collected through documentary analysis, direct observation and productive records, comparing the results obtained before and after the implementation of a digital registration system. Data processing was performed using Microsoft Excel and SPSS, applying the Shapiro–Wilk normality test and the Pearson and Spearman correlation coefficients, depending on the distribution of the data. The results showed a significant reduction in specific operating costs after digitalization. Administrative costs decreased from S/ 298.02 to S/ 12.81 per month (−95.7%), logistics costs were reduced by −66.7% and costs associated with administrative inputs were eliminated by −100%, with the total expenditure for these items going from S/ 3,857.06 to S/ 134.44. However, no statistically significant relationship was found between digitalization and total cost of production (r = 0.163; p = 0.758). In terms of profitability, quantifiable improvements were observed: the profit/cost ratio increased from 1.31 to 1.33, the gross margin from 23.8% to 24.9%, and the profit per pig from S/ 243.3 to S/ 254.6. Likewise, a positive and significant relationship between digitalization and profitability was confirmed (Rho = 0.878 to 1.000; p < 0.05). It is concluded that digitalization is significantly related to the profitability of pig production, although not to the total cost in the period evaluated.